2024
DOI: 10.1186/s44158-024-00139-5
|View full text |Cite
|
Sign up to set email alerts
|

Update on vitamin D role in severe infections and sepsis

Salvatore Lucio Cutuli,
Elena Sancho Ferrando,
Fabiola Cammarota
et al.

Abstract: Severe infections frequently require admission to the intensive care unit and cause life-threatening complications in critically ill patients. In this setting, severe infections are acknowledged as prerequisites for the development of sepsis, whose pathophysiology implies a dysregulated host response to pathogens, leading to disability and mortality worldwide.Vitamin D is a secosteroid hormone that plays a pivotal role to maintain immune system homeostasis, which is of paramount importance to resolve infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Our findings are in accordance with previous data that demonstrate an increased prevalence of hypovitaminosis D in critically ill cases [ 11 , 19 , 20 , 28 ]. Evidence also suggests that decreased vitamin D is a risk factor for sepsis and a poor outcome [ 8 , 9 , 13 , 14 , 16 , 20 ]. A recent meta-analysis of 8 studies with 1736 cases showed that decreased 25(OH)D at admission was independently linked to an increased mortality in cases with sepsis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in accordance with previous data that demonstrate an increased prevalence of hypovitaminosis D in critically ill cases [ 11 , 19 , 20 , 28 ]. Evidence also suggests that decreased vitamin D is a risk factor for sepsis and a poor outcome [ 8 , 9 , 13 , 14 , 16 , 20 ]. A recent meta-analysis of 8 studies with 1736 cases showed that decreased 25(OH)D at admission was independently linked to an increased mortality in cases with sepsis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, vitamin D stimulates macrophages, induces regulatory T cells and Th2 response, inhibits B lymphocyte proliferation and differentiation, modulates dendritic cell maturation and tumor necrosis factor expression, suppresses pro-inflammatory cytokines and induces the synthesis of anti-inflammatory cytokines [ 11 , 12 ]. Additionally, vitamin D promotes barrier function and production of antibacterial peptides and reactive oxygen species [ 13 ]. Clinical studies suggest that hypovitaminosis D is a risk factor for bacterial and viral respiratory infections and sepsis [ [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%